Bermain atau Sepenuhnya Meninggalkan Musik: Dua Narasi Artis Hijrah pada Hukum Bermain Musik - As'ad, Muhammad; Lazib, Ihyaul; Ramdhani, Iryan (Tebuireng: Journal of Islamic Studies and Society, 2023)
This article explores two narratives of hijra celebrities regarding whether they completely abandon playing music or continue to play it under certain conditions after experiencing a spiritual transformation (hijra). The data of this article was collected through online sources such as news articles, social media posts, and videos that were relevant to the research question. The two celebrities, Mohammad Kautsar Hikmat (UKI) and Derry Sulaiman, were both previously involved in the Indonesian music industry and have now adopted differing attitudes towards music after their spiritual transformation. Uki chose to leave the music industry as he interpreted his spiritual transformation, or hijrah, as requiring him to withdraw from elements that he believed could hinder his spiritual growth such as music. He interacted with the Salafi community who promote a literal interpretation of Islam and believe music is a hindrance to spiritual growth. Derry, on the other hand, chose to continue his involvement in the music industry as he believed that music could be a tool for spreading positive messages and preaching the word of Islam without interfering with his religious duties. He interacted with a more diverse Muslim community inlcuding Nahdlatul Ulama (NU) and Muhammadiyah that demonstrated how Islam can be practiced in various ways and adapt to cultural contexts. The article uses Bernard Weiner's interpersonal and intrapersonal theory to explain how the two celebrities interpreted the role of music in their religious lives. The findings show the importance of understanding both interpersonal and intrapersonal factors when exploring how celebrities interpret and apply religious principles to their lives. This article provides important insights into the complexities of the relationship between music and Islam, and how spiritual transformation can affect an individual’s view on music.